RELATIONSHIP BETWEEN RAINFALL AND LAND COVER ON THE NUMBER OF HOTSPOTS IN LORE LINDU NATIONAL PARK - Fadjri Maarif; Cesar Andi Mappatoba (BIOTROPIA, 2024)
Forest and land fires in Indonesia need concern in handling it, specifically in conservation areas. Lore Lindu National Park (TNLL) is a conservation area that plays a role in preserving endemic plants and animals and their habitats. Research on the factors that influence forest fires in TNLL needs to be carried out to protect and prevent the risk of forest fires to protect the ecosystem. This study aims to analyze the relationship between rainfall and land cover on the number of hotspots as an indicator of forest fires in TNLL in 2017-2021. Thus, preventive strategies can be carried out as early as possible to prevent forest fires. This research was conducted by analyzing spatially and statistically 2017-2021 rainfall data in Sigi and Poso Regencies, hotspot data from the TERRA/AQUA, SNPP, and MODIS-NASA satellite in 2017-2021 in TNLL, and TNLL land cover data. In statistical analysis, rainfall data for hotspots was analyzed using Bivariate Pearson, and land cover data for hotspots was analyzed spatially using ArcMap. The results showed 55 hotspots in TNLL from 2017-2021. The Bivariate Pearson correlation test results between rainfall and hotspots are -0.028. The relationship between rainfall and hotspots shows a non-directional correlation. The lower the rainfall intensity, the more hotspots are found. Spatially, the highest number of hotspots occurred in areas with the land cover of secondary dryland forest types, with a total of 29 spots.